2000
DOI: 10.1002/1521-3765(20001201)6:23<4305::aid-chem4305>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Metallorganic Routes to Nanoscale Iron and Titanium Oxide Particles Encapsulated in Mesoporous Alumina: Formation, Physical Properties, and Chemical Reactivity

Abstract: Iron and titanium oxide nanoparticles have been synthesized in parallel mesopores of alumina by a novel organometallic "chimie douce" approach that uses bis(toluene)iron(0) (1) and bis(toluene)titanium(0) (2) as precursors. These complexes are molecular sources of iron and titanium in a zerovalent atomic state. In the case of 1, core shell iron/iron oxide particles with a strong magnetic coupling between both components, as revealed by magnetic measurements, are formed. Mössbauer data reveal superparamagnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…When using this approach within the mesospace provided by porous alumina films, strongly magnetically coupled metal/metal oxide systems as well as pure single-phase metal oxides are accessible. [14] The homogeneous and tunable size, as well as the aqueous acidic atmosphere of the alumina mesopores, have proven to be unique as a reaction partner offering both confinement and special reaction conditions for metal oxide formation in their interior. Incorporation of organometallics, followed by subsequent reaction of a defined molecular organometallic entity, has so far not been reported for this type of host.…”
Section: Magnetic Core/shell Particlesmentioning
confidence: 99%
See 2 more Smart Citations
“…When using this approach within the mesospace provided by porous alumina films, strongly magnetically coupled metal/metal oxide systems as well as pure single-phase metal oxides are accessible. [14] The homogeneous and tunable size, as well as the aqueous acidic atmosphere of the alumina mesopores, have proven to be unique as a reaction partner offering both confinement and special reaction conditions for metal oxide formation in their interior. Incorporation of organometallics, followed by subsequent reaction of a defined molecular organometallic entity, has so far not been reported for this type of host.…”
Section: Magnetic Core/shell Particlesmentioning
confidence: 99%
“…The subsequent formation of a two-layer-like particle, comprising an iron oxide-/hydroxide-rich shell near the pore surface with an inner, metallic-iron core, can be deduced from magnetic, Mössbauer, extended X-ray absorption fine structure (EX-AFS), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) measurements. [14] From such studies, the oxide phase can be identified as low-crystallinity ferrihydrite oxide with low-ordering and substantial defect sites. [14] Defects in nanocrystals have already been recognized to be important in many aspects of their surface chemistry.…”
Section: Magnetic Core/shell Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the impregnation of mesoporous alumina by a solution of bis(toluene) titanium leads to a black metallic deposit which, after oxidation at 400°C, leads to the growth of TiO 2 nanoparticles [87]. In organic solution bis(cyclooctatetraene) titanium complex (Ti(C 8 H 8 ) 2 ) reacts with dry DMSO to yield a precipitate of amorphous TiO 2 .…”
Section: Metal Oxidesmentioning
confidence: 99%
“…On the other hand, the absorption edge was shorter than that of the bulk TiO 2 because the blue shift is caused by the quantum size effect, which has already been explained. [16][17][18][19] The size of TiO 2 is sufficiently small because it was immobilized into nanopores (pore diameter: approx. 10 nm) of the anodic porous alumina, so it is possible that the quantum size effect is manifested in TiO 2 /Al 2 O 3 .…”
Section: Characterization Of Tio 2 /Al 2 Omentioning
confidence: 99%